Is calcium deficiency the real cause of bitter pit? A review - Torres, Estanis; Kalcsits, Lee; Nieto, Luís Gonzalez (Frontiers in Plant Science, 2024)
Bitter pit is a disorder affecting the appearance of apples. Susceptibility is genetically controlled by both the cultivar and rootstock with both environmental and horticultural factors affecting its severity and proportional incidence. Symptoms appear more frequently at the calyx end of the fruit and consist of circular necrotic spots which take on a "corky" appearance being visible through the peel. Bitter pit may develop before harvest, but is not picked, or after harvest reducing the proportions of marketable fruit. In this review, current knowledge of the factors associated with the occurrence of bitter pit in apples are summarized and discussed along with their interactions with Ca uptake and distribution to fruit. This disorder has been previously linked with localized Ca deficiencies in fruit during its development. However, these relationships are not always clear. Even with over a century of research, the precise mechanisms involved in its development are still not fully understood. Additional factors also contribute to bitter pit development, like imbalances of mineral nutrients, low concentration of auxins, high concentration of gibberellins, changes in xylem functionality, or physiological responses to abiotic stress. Bitter pit remains a complex disorder with multiple factors contributing to its development including changes at whole plant and cellular scales. Apple growers must carefully navigate these complex interactions between genetics, environment, and management decisions to minimize bitter pit in susceptible cultivars. Accordingly, management of plant nutrition, fruit crop load and tree vigor still stand as the most important contributions to reducing bitter pit development. Even so, there will be situations where the occurrence of bitter pit will be inevitable due to cultivar and/or abiotic stress conditions.